PENGELOLAAN PENDIDIKAN DALAM UPAYA PEMBERDAYAAN GURU SEKOLAH DASAR BERBASIS SOFT SKILL DI KOTA JAMBI - sri marmoah (Jurnal Ilmiah Dikdaya, 2016)
The background study of this research is to develop a teaching model of soft skill and also to improve teachers’ soft skills who want to enter the world of work. In this research study, the researcher tries to see and analyze the prevailing condition teachers in the field of education. The goals of this research are developing of skills activity and knowing the educational administration for teachers. The design of this research was descriptive qualitative research. The data for this research was collected through observation and questionnaire. The result analysis can be concluded as follows: First, the educational management of elementary school teachers based on soft skill are still effective; Second, based on the results of research can be concluded that the educational management of elementary school teachers based on soft skill, the need for education mismatching with their need. Third, average teachers at the elementary school have medium motivation to develop of their soft skill; this is evidenced from the result of questionnaire that spread to these teachers. Based on the result, eight teachers were known from total 15 teachers have medium level of motivation. The results of the percentage analysis for experiments class for the improvement of teachers’ soft skills showed that the average of four soft skills competencies, include strategic capabilities, communication skills, interaction skills, and psychological skills, soft skills competencies teachers at the level of effective. The indicators shown that the soft skill teachers’ competencies are still low and quite lack, therefore empowering teachers in the elementary school can be improved to empowerment both in personal competence and social competence.